Discovering the Learning Voice: The Power of Transmodality in the Process of Self-Authorship - Ott, Mary; Robertson, Jessica (Language and Literacy / Langue et littératie, 2025)
Literacy education can play a vital role in positive identity formation across the life span. This paper conceptualizes the influence of transmodality in the psychological process of self-authorship. Utilizing a method of narrative inquiry to revisit a course on life-long learning and meaning-making, we explore an example of transformative change in how one student came to trust their voice as a learner and educator. Our findings show that humanizing pedagogy that makes space for vulnerability to revisit life events through different modes and media affords opportunities to revise understandings of the past and envision more positive futures. The study contributes theory and examples of how processes involved in transmodal meaning-making may help young people and adults discover more joyful ways of being.